1997
DOI: 10.1111/j.1744-7429.1997.tb00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Seed Size, Germination and Seed Viability of Tropical Tree Species in Southern India1

Abstract: Seed weight, days to germination and seed viability were observed for 99 species growing in the Western Ghats of Karnataka, India. Seed size was strongly correlated with days to germination; smaller seeds germinated faster than larger seeds. Species which flowered during the rainy season had lighter seeds than species which flowered during the dry season. It was also found that seed size and viability of seeds were related to the season of fruiting. Species which fruit during the rainy season had heavier seeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 16 publications
8
59
1
4
Order By: Relevance
“…Stem characters among provenances is due to resource availability at the time of fruiting and so to seed size. This in turn could be due to different environments at the geographic origins of each seed and seasonal variables (Murali, 1997). Loha et al (2009) also observed significant variation in seed size traits of Cordia Africana.…”
Section: Discussionmentioning
confidence: 99%
“…Stem characters among provenances is due to resource availability at the time of fruiting and so to seed size. This in turn could be due to different environments at the geographic origins of each seed and seasonal variables (Murali, 1997). Loha et al (2009) also observed significant variation in seed size traits of Cordia Africana.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the energy potential of large seeds is considered to emerge better in most of the habitats (Stevenson et al, 2005). Large seeds show better germination parameter and establishment potential of seedlings as compared with medium and small seeds (Murali, 1997;Negi and Todaria, 1997;Khan and Shankar, 2001;Mwase and Mvula, 2011). Consideration of seed traits may be a useful aspect for propagation and conservation of valuable plants ( Khurana and Singh, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Morphometric and physiological characteristics of seeds influence germination (Kastori, 1984). Variations in seed weight are positively correlated with variability of seeds (Murali, 1997;Stejskalova et al, 2014). There is a relationship between seed weight and germination, but it differs between species.…”
Section: Introductionmentioning
confidence: 99%